Factors behind successful alliances for local development. Comparative experiences of Spain and Peru (Journal of Business, Universidad del Pacífico (Lima, Peru), 2009)
Alliances are formed in order to overcome the constraints partners face to achieve certain goals. While the goal is to promote local development, it requires the participation of stakeholders: private sector, local government, civil associations and community groups, among others. This article seeks, through the comparative analysis of three experiences of local development led by the district of Villa El Salvador (Lima - Peru), the mining company Yanacocha (Cajamarca - Peru) and the Spanish Agency for Development Iraugi Lantzen (Basque Country - Spain), to identify the factors of successful cooperation agreements for local development. it is believed that a better understanding of the factors associated with effective partnerships could help those who seek the challenge of looking for possible partners, as well as those concerned with theeffective management of partnerships in place. The case of Villa El Salvador showed how government support was fundamental in the establishment of the district, but the achievements of this group could not be explained without the active participation of the community. On the other hand, the experience of the company Yanacocha reminds the reader that there is still a big gap to fill in Peru in terms of articulating the joint efforts between private enterprises and stakeholders, and it is vital to learn from the experiences of those who have gone through part of this path. A different case is shown in the experience of the Spanish Agency, Iraugi Lantzen, highlighting the challenges and opportunities that arise from a concerted action between municipal entities pursuing local development. Overall, it can be said that although there are context and situational conditions that favor the development of alliances for development, there are other factors that mediate the success of partnerships. The case studies showed that the most successful cooperation experiences are those in which there are key individuals with a sense of leadership who manage connect both personally and emotionally with each other with the purpose of creating an alliance.